The return to 1980 stratospheric halogen levels: a moving target in ozone assessments from 2006 to 2022 - M. J. Lickley; M. J. Lickley; J. S. Daniel; L. A. McBride; L. A. McBride; R. J. Salawitch; R. J. Salawitch; R. J. Salawitch; G. J. M. Velders; G. J. M. Velders (Atmospheric Chemistry and Physics)
The international scientific assessment of ozone depletion is prepared every 4 years to support decisions made by the parties to the Montreal Protocol. In each assessment an outlook of ozone recovery time is provided. The year when equivalent effective stratospheric chlorine (EESC) returns to the level found in 1980 is an important metric for the recovery of the ozone layer. Over the past five assessments, the expected date for the return of EESC to the 1980 level, for mid-latitudes, was delayed, from the year 2049 in the 2006 assessment to 2066 in the 2022 assessment, which represents a delay of 17 years over a 16-year assessment period. Here, we quantify the primary drivers that have delayed the expected EESC recovery date between each of these assessments. We find that by using identical EESC formulations, the delay between the 2006 and 2022 assessments' expected return of EESC to 1980 levels is shortened to 12.6 years. Of this delay, bank calculation methods account for ∼ 4 years, changes in the assumed atmospheric lifetime for certain ozone-depleting substances (ODSs) account for ∼ 3.5 years, an underestimate of the emission of carbon tetrachloride accounts for ∼ 3 years, and updated historical mole fraction estimates of ODSs account for ∼ 1 year. Since some of the underlying causes of these delays are amenable to future controls (e.g., capture of ODSs from banks and limitations on future feedstock emissions), it is important to understand the reasons for the delays in the expected recovery date of stratospheric halogens.